Beyond Equality Before the Law: Konstruksi Perlindungan Hak Perempuan dalam Undang-Undang Cipta Kerja Perspektif Hak Asasi Manusia - Bella Ayu Aranta; Muhammad Adil; K.A. Bukhori (CV. Ulil Albab Corp, 2026)
Law No. 11 of 2020 concerning Job Creation, whose validity was later reaffirmed through Law No. 6 of 2023, has brought about a fundamental shift in labor law regulations in Indonesia. This legislation was designed within a deregulation policy framework with an emphasis on increasing labor market flexibility as an instrument to strengthen the investment climate and stimulate national economic growth. However, this policy direction raises normative issues, particularly regarding the certainty of protecting the rights of women workers, who are structurally vulnerable in employment relations. Within the framework of human rights, as affirmed in Law Number 39 of 1999 concerning Human Rights, legal protection cannot be understood solely as equal treatment before the law. Furthermore, legal protection necessitates the application of substantive justice that takes into account the differences in social, biological, and economic conditions inherent in vulnerable groups. Departing from this perspective, this research aims to examine the normative construction of women's rights protection in the Job Creation Law by positioning the human rights regime as the analytical framework and assessing the extent to which the regulation accommodates the principle of substantive justice in protecting women workers. This study employs normative legal research methods with a statutory and conceptual approach, complemented by a review of the Constitutional Court's ruling on the Job Creation Law. The research findings indicate that the provisions for protecting women's rights in the Job Creation Law still rely on a formal equality approach that tends to be gender-neutral. This approach fails to fully address the specific protection needs based on gender vulnerabilities, resulting in the suboptimal fulfillment of women workers' human rights within the national labor law system.